Social Dysfunction in Patients with Chronic Illness - Khawaja, Hamid Rashid; Hamid, Muneeza (International Journal of Pathology, 2018)
Background: Social dysfunction refers to an undesirable behavior pattern or disturbed social interaction,performance, self-perception and self-system which results in decreased self-care and increaseddistress in the life of individual. Chronic illness is the major reason behind social dysfunction. Both, thepsychiatric chronic illness (depression, anxiety, psychotic disorders) and non-psychiatric chronic illness(diabetes, stroke, heart disease etc.) can lead to social dysfunction.Objectives: The study has been carried out for the purpose of exploring the level of social dysfunctionamong patients with chronic illness and to analyze the demographic factors associated with it.Methodology: A total number of 300 patients of chronic illness were selected from psychiatric andmedical OPDs of Abbas Institute of Medical Sciences (AIMS) Muzaffarabad using purposive samplingtechnique. Socio-demographic data was collected and then a 21-item standard scale of Linn (social dysfunctionrating scale) was used to measure the social dysfunction of patients. Medical records of patientswere also observed.Results: It was found that 74% of the patients of chronic illness suffer from mild to severe degree ofsocial dysfunction (where criteria for chronic illness=1 year or more). Among these, 47% had moderatelevel of social dysfunction, while 6% had severe degree of social dysfunction. Results also indicate that35% of the patients had psychiatric illness (among which 20.3% had depression) while 65% had nonpsychiatricchronic illness (among which 9.9% had Ischemic Heart Disease). 23% comorbidity was present.Most of the chronically ill patients were females (57%). 67% of the patients were on regular treatmentfor their chronic illness.Conclusion: There exists a high level (74%) of social dysfunction among patients with chronic illness.Both psychiatric and non-psychiatric chronic illnesses lead to social dysfunction. The rate of social dysfunctionwas found higher among psychiatric illnesses as compared to non-psychiatric illnesses. Thestudy also highlighted the issue that social functioning of the patients is generally ignored when treatmentplans are formulated; which is the major factor behind high rate of social dysfunction in chronicillness. Other factors; age, employment status, gender and education, are also associated with socialdysfunction. Counselling services need to be developed in hospitals in order to improve the level ofsocial functioning of patients with chronic illnesses.